Efeito do teor de água na avaliação da compactação do solo causada pelo tráfego agrícola e seu reflexo nos atributos físicos do solo - Fernandes, Barbara Barreto [UNESP] (2015)
The changes caused by human activities such as machinery traffic directly affect soil structure, therefore, the importance of assessing soil compaction due to agricultural traffic, as well as the magnitude of the impact of the wheelset on the physical quality of the soil. The study aimed to evaluate the influence of water content in soil penetration resistance evaluation measured by the soil Cone Index (CI), the occurrence and distribution of compression along the soil profile, caused by agricultural traffic, as well as the resulting consequences on soil physical properties. The experiment area was at Lageado Experimental Farm, UNESP/FCA, Botucatu/São Paulo, two different soil type was used, Nitossolo Vermelho distroférrico (NVd) clayey, 50% clay content and Latossolo Vermelho (LV) of medium texture, 25% clay content. Was used an randomized experimental design with the following compaction treatments: T0 = 0; T1 = 1; T2 = 2; T3 = 3; T4= 5 and T5 = 10 consecutive passes of an tractor. An hydraulic-electronic penetrometer was used to measure the soil resistance at 0-0.10; 0.10-0.20; 0.20-0.30 and 0.30-0.40 m in 4 different water content ranging from 17.1 to 24.5% for NVD and 10 to 17.8% for LV. It was also determined the following attributes: soil repression, water infiltration into the soil, bulk density and porosity. The major soil penetration resistance values were detected near the ground shrinkage limit and the treatment with increased intensity agricultural traffic, already in high moisture soil conditions, the soil penetration resistance values were reduced being considered not hindering the growth of roots. The clay soil proved to be the most sensitive to the effect of water content in soil compaction evaluation, the greater variation among samples collected with water content between field capacity (FC) and permanent wilting point (PWP) ...